2017
DOI: 10.1177/0954406216688495
|View full text |Cite
|
Sign up to set email alerts
|

Axial groove casing treatment in an automotive turbocharger centrifugal compressor

Abstract: The automotive market is continually driving the suppliers of turbochargers to push their designs into new unexplored realms. The most recent request is to have improvements to the surge margin at higher pressure ratios due to the demands of modern Diesel and gasoline engines. This study looked back at historic casing treatments and investigated the concept of axial grooves being applied to the shroud of a centrifugal compressor. This paper presents a literature review of previous centrifugal compressor casing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…More sophisticated configurations have been studied recently. Harley et al [113] showed the potential of axial grooves to achieve similar results to a ported shroud but with a more packaged configuration; the axial groove helped to reduce the impeller passage's reverse flow by maintaining the blade load, so that the inlet velocity triangle was modified. The system consisted of a single opening on the inducer shroud, where grooves were designed to guide the recirculating flow with the minimum losses.…”
Section: Passive Flow Control Methodsmentioning
confidence: 99%
“…More sophisticated configurations have been studied recently. Harley et al [113] showed the potential of axial grooves to achieve similar results to a ported shroud but with a more packaged configuration; the axial groove helped to reduce the impeller passage's reverse flow by maintaining the blade load, so that the inlet velocity triangle was modified. The system consisted of a single opening on the inducer shroud, where grooves were designed to guide the recirculating flow with the minimum losses.…”
Section: Passive Flow Control Methodsmentioning
confidence: 99%
“…The axial groove consists of a similar solution to the previous but more compact: there is a single opening on the inducer shroud where grooves are designed to guide recirculating flow with minimum losses. The benefits of axial grooves has been studied is numerical works [23,24]. Finally, circumferential grooves can be installed at the diffuser to alleviate blockage in vaned diffusers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is precisely for these two reasons that our subsequent research and application of flow control will also be established at the blade tip. At present, the applications applied to the tip area of centrifugal compressor are various, among which the most widely used is casing treatment, including selfrecirculation casing treatment (SRCT) [24], circumferential grooves [25], bleed slots [26], axial groove [27], nonaxisymmetric casing treatment [28], and ported shroud [29]. Except for casing treatment, the application of some other control methods, such as air injection [30], suction [31], and blade tip winglet [32], is relatively less.…”
Section: Introductionmentioning
confidence: 99%